EFL university teachers’ perspectives in written corrective feedback and their actual applications - Windy Wahju Purnomo; Yazid Basthomi; Johannes Ananto Prayogo (Institute of Advanced Engineering and Science, 2021)
This study aimed to investigate the English as a foreign language (EFL) university teachers’ perspective and their actual applications in providing written corrective feedback to the writing errors made by the EFL university students and their correlation. The study was based on 80 responses of a Google-Form survey distributed to EFL university teachers with various teaching experiences from the most parts of Indonesia. Correlational design was used in this research. Descriptive statistics and Pearson’s correlation tests were used to analyze data. The results indicated that the majority of teachers had perspectives that it is valuable to provide and vary the strategies of written corrective feedback. In addition, the teachers mostly applied both direct and indirect feedback in various strategies and they only sometimes provided corrections in all aspects of errors and reformulation. It was also found out that the Indonesian EFL university teachers’ perspectives in the written corrective on students’ writing errors highly correlated with their actual applications. The results of the study provide both theoretical and pedagogical implications. Theoretically, it enriches the body knowledge of feedback and EFL writing. Pedagogically, EFL teachers are also suggested to improve their knowledge on various feedback techniques and apply it in their classroom teaching and learning process.